The Role and Benefits of Sharia Microinsurance for MSME Economic Resilience - Lutfiyah, Rayi Alya (Jurnal Iqtisaduna, 2025)
This research aims to analyze the role of sharia microinsurance in reducing economic risk and its benefits in increasing the economic resilience of MSMEs in the KUR program. This research uses descriptive qualitative type with data collection sources through interviews, observation, and documentation. The data analysis technique used is the Miles and Huberman model with the NVivo 12 pro software tool. The results showed that sharia micro insurance not only plays a role in helping MSMEs to obtain financing that has a guarantee on the customer's life but also has a mechanism that is in accordance with sharia principles through tabarru' and wakalah bil ujrah contracts as regulated in DSN-MUI Fatwa No. 21/DSN-MUI/X/2001 concerning General Guidelines for Sharia Insurance. Sharia Micro Insurance helps mitigate risk and provide financial protection, enabling MSMEs to expand their businesses, diversify their products, and increase their income. These findings encourage policies to increase access and socialization of Islamic microinsurance for MSMEs.